Corporate earning performance in Malaysia from 1993 to 2000: a study of the construction sector / Abdul Razak Ali - Ali, Abdul Razak (2002)
This study is aimed at determining and analysing construction company’s earning performance in Malaysia during the period 1993 - 2000. Two models have been selected to test and analyse that performance (multiple regression analysis and hypothesis testing). The findings have revealed that GDP is found to be the most significant independent variables in influencing the changes and variation of their earning. On the other hand, CPI and interest rate are of low significant. The weaknesses of this study is the attention and focus only on the economic variables which is external and no consideration at all on the internal variables for example, the organizational and management capability. For example, management influences on corporate earning performance may vary with organizational characteristics and managerial leadership behavior, one manager may exploit an economic movement opportunity, while another leader may forgo such an opportunity or adapt slowly to it. A manager is important in times of organizational growth, development and crisis, for most part of the organizations require maintenance, and the corporate manager will therefore make little difference to their performance. Therefore the study recommends to other future student and researcher to include the organizational and management capability which is internal to the firm as one of the independent variables.